Central European EU Accession and Latin American Integration: Mutual Lessons in Macro-Economic Policy Design - George Kopits (Oesterreichische Nationalbank (OeNB), 2002)
Design options in exchange rate, monetary and fiscal policies, are explored for economies in Central Europe and Latin America that aspire to engage in monetary unification. Recent experience in these regions suggests that, absent a model of institutional harmonization and a road map for policy convergence, Latin American economies would benefit from following internally consistent macroeconomic policies—possibly in the context of a rules-based framework—and from adopting widely accepted standards of best practice. Unilateral adoption of a hard currency (dollarization or euroization) tends to be counterproductive unless it is supported by fiscal discipline and wage flexibility. Empirical evidence is presented on the effect of expected monetary unification on sovereign risk.
Keywords: E61; E63; F33; 330; Economic and Monetary Union; Policy Convergence; Determinants of Sovereign Risk